Conversation with Carlos Pereda in Mexico not giving in to the post-truth temptation - Pereda, Carlos 1944-; Jiménez Cataño, Rafael 1960- (2019)
There have always been lies and deception. The current peculiarity of this reality is the vague generalized conviction that thought and discourse operate in a vacuum, that there is no world to which they can be compared. However, it is clear that truth continues to matter to us and that the instinct to trust, typical of the social nature of human beings, makes the media's lack of reliability painful. A very pure or "binary" rationality does not offer any answers. A more integral vision of the knowing subject is necessary. This subject would not enter into relation with others if he or she were merely cognizant. Relation implies the mutual recognition, legitimization, and presupposition of goodwill. The climate created by post-truth requires an education for truth, which is not only for the formation of a critical sense, but also in order to learn to trust and believe, which are both deeply human acts.
Keywords: Carlos Pereda; Autonomy; Fake News; Interpretation; principle of charity; Trust; Interview